The brain-heart connection: Value of concurrent ECG and EEG recordings in epilepsy management - Jeremy D. Slater; Selim Benbadis; Richard L. Verrier (Epilepsy & Behavior Reports)
Concurrent electrocardiogram (ECG) and electroencephalogram (EEG) recording both ictally and interictally has significant value in the comprehensive management of epilepsy. This review highlights the diagnostic utility of simultaneous ECG and EEG monitoring in differentiating between epileptic and cardiac events, detecting cardiac abnormalities, and identifying autonomic dysfunction. The critical role of this combined approach to defining the mechanisms underlying cardiac morbidity and sudden cardiac death in patients with epilepsy and in guiding therapeutic interventions is underscored. The “Epileptic Heart Syndrome” is examined, illustrating how chronic epilepsy can adversely affect cardiac structure and function, leading to increased risk for interictal cardiac arrhythmias, morbidities, and mortality. The findings emphasize the need for standardized protocols for routine concurrent ECG and EEG recording in epilepsy monitoring units both ictally and interictally to ensure comprehensive patient care, improve diagnostic accuracy, and potentially reduce epilepsy-related morbidity and mortality. Future research directions are proposed to address existing gaps and to advance the technology and methodology for concurrent monitoring including wearable and computer-based monitoring systems.